Health‐related quality of life in patients with bronchiolitis obliterans - Edgar E. Sarria; Eduardo Mundstock; Denise G. Machado; Helena T. Mocelin; Gilberto B. Fischer; Silvana P. Furlan; Ivan C.F. Antonello; Ricardo Stein; Rita Mattiello (Brazilian Society of Pediatrics, 2018)
Objective: To evaluate the overall health‐related quality of life in patients with bronchiolitis obliterans. Methods: Participants with a diagnosis of post‐infectious bronchiolitis obliterans, who were being followed‐up at two specialized outpatient clinics of Pediatric Pulmonology in Porto Alegre, Brazil, and controls aged between 8 and 17 years, of both genders, were included in the study. Controls were paired by gender, age, and socioeconomic level in relation to the group of participants with post‐infectious bronchiolitis obliterans. The version of the Pediatric Quality of Life Inventory (PedsQ) tool validated for Brazil was applied for the assessment of Health‐related Quality of Life, through an interview. The comparison of the Health‐related Quality of Life means between the groups was performed using Student's t‐test for independent samples and the chi‐squared test, for categorical variables. Results: 34 patients diagnosed with post‐infectious bronchiolitis obliterans and 34 controls participated in the study. The mean age of the children included in the study was 11.2 ± 2.5 years, and 49 (72%) of them were males. The groups showed no significant differences in relation to these variables. The quality of life score was significantly and clinically lower in the post‐infectious bronchiolitis obliterans group when compared with controls in the health (72.36 ± 15.6, 81.06 ± 16.4, p = 0.031) and school domains (62.34 ± 20.7, 72.94 ± 21.3, p = 0.043), as well as in the total score (69.53 ± 14.9, 78.02 ± 14.8, p = 0.024), respectively. Conclusion: Patients with post‐infectious bronchiolitis obliterans presented lower health‐related quality of life scores when compared with healthy individuals in the total score and in the health and school domains. Resumo: Objetivo: Avaliar a qualidade de vida relacionada à saúde geral em participantes com bronquiolite obliterante. Métodos: Foram incluídos no estudo participantes com diagnóstico de bronquiolite obliterante pós‐infecciosa que estavam em acompanhamento em dois ambulatórios especializados de pneumologia pediátrica em Porto Alegre, Brasil e controles, entre 8 e 17 anos, de ambos os sexos. Os controles foram pareados por sexo, idade e nível socioeconômico em relação ao grupo de participantes com bronquiolite obliterante pós‐infecciosa. Para avaliação da Qualidade de Vida Relacionada à Saúde geral foi aplicado a versão validada para o Brasil do instrumento PedsQL (Pediatric Quality of Life Inventory), por meio de entrevista. A comparação entre as médias da Qualidade de Vida Relacionada à Saúde entre os grupos foi realizada mediante o teste t para amostras independentes e para as variáveis categóricas por teste qui‐quadrado. Resultados: Participaram do estudo 34 pacientes com diagnóstico de bronquiolite obliterante pós‐infecciosa e 34 controles. A média da idade das crianças incluídas foi de 11,2 ± 2,5 anos e 49 (72%) deles eram do sexo masculino. Os grupos não apresentaram diferenças significativas em relação a essas variáveis. O escore de qualidade de vida foi significativamente e clinicamente menor no grupo bronquiolite obliterante pós‐infecciosa em comparação com o controle nos domínios saúde: (72,36 ± 15,6; 81,06 ± 16,4; p = 0,031); escolar: (62,34 ± 20,7; 72,94 ± 21,3; p = 0,043) e no escore total (69,53 ± 14,9; 78,02 ± 14,8, p = 0,024), respectivamente. Conclusão: Os pacientes com bronquiolite obliterante pós‐infecciosa apresentam escores de qualidade de vida relacionados à saúde menor do que indivíduos saudáveis no escore total e nos domínios saúde e escolares. Keywords: Health‐related quality of life, Bronchiolitis obliterans, Children, Palavras‐chave: Qualidade de vida relacionada à saúde, Bronquiolite obliterante, Crianças